Notice of meeting
043-0010-001 file SPANISH MEDICAL AID COMMITTEE President: Rt. Hon. LORD ADDISON Vice-Presidents: Dr. CHARLES BROOK. L.C.C. Dr. DAVID FORSYTH VICTOR GOLLANCZ Professor JULIAN HUXLEY Rt. Hon. Sir WILLIAM JOWITT, K.C. Sir WALTER T. LAYTON The EARL OF LISTOWEL Miss MEGAN LLOYD GEORGE, M.P. TOM MANN D.N. PRITT, K.C., M.P. Miss ELEANOR RATHBONE, M.P. Miss ESTHER RICKARDS, L.C.C. JOS. ROBINSON, M.D. Dr. MAUDE ROYDEN Sir ARCHIBALD SINCLAIR, M.P. BEN TILLETT Dr. JANET VAUGHAN ALFRED M. WALL Miss REBECCA WEST Chairman: Dr. H.B. MORGAN, M.D. Vice-Chairman: Dr. SOMERVILLE HASTINGS, L.C.C. Treasurers: Viscountess HASTINGS W. LOCKYER, J.P. Professor J.R. MARRACK, M.D., D.S.O. Hon. Secretary: Mrs. LEAH MANNING, J.P. Organising Secretary: GEORGE JEGER, J.P. Note New Address: 69, GT. RUSSELL ST., W.C.1. Telephones: HOLborn 1866 0605 June 9th 1939 You are requested to attend a meeting of the Organising Sub-Committee on Wednesday next the 14th June at 8.0 p.m. This will be followed by a meeting of the main Committee at 8.45 p.m. 292/946/43/10